Improving employee and workplace performance via lean manufacturing practices: A case study in textile company - Hanifah, Hatif; Lee, Khai Loon; Gusman, Nawanir (Penerbit Universiti Malaysia Pahang, 2024)
This study explores the possibility of enhancing employee and workplace performance by implementing lean manufacturing practises in a textile industry. It addresses the the limited availability of empirical data concerning lean practices, with a particular focus on the textile industry. Qualitative approaches were employed involving direct observations and in-depth interviews with important stakeholders, followed by a thematic analysis of the data. The findings highlight the effects of lean manufacturing practises (Just-in-Time (JIT), flexibility, and continuous improvement) on worker performance, workplace productivity, quality, and overall organisational performance. The outcomes of this research offer valuable insights and practical recommendations for textile companies aiming to enhance their employee and workplace performance through the adoption of lean manufacturing practices. Such implementation will help to reduce lead time, improve customer satisfaction, and increase productivity and efficiency.